Lack of apoptosis in PanIN-1 and PanIN-2 lesions associated with pancreatic ductal adenocarcinoma is not dependent on K-ras status - Lüttges, Jutta; Neumann, Svenja; Jesenofsky, Ralf; Borries, Vivian; Löhr, J.-Matthias; Klöppel, Günter (Pancreas, 2003)
Introduction: K-ras mutations are present in most ductal adenocarcinomas (DACs) of the pancreas and may also be found in ductal precursor lesions and even in normal ductal epithelium. The question is addressed whether mutated K-ras interferes with the regulation of apoptosis or proliferation. Methodology: In 50 Whipple resection specimens, tissue adjacent to DACs was histologically screened for ductal lesions that were classified as pancreatic intraepithelial neoplasia (PanIN) according to WHO criteria. PanIN lesions were microdissected and analyzed for K-ras mutations by means of a nested PCR. Apoptosis was identified by the TUNEL method. Proliferation and the expression of p53 and Bcl-2 were immunohistochemically determined. Results: On average, 30% of PanIN-1A and B lesions showed mutated K-ras. In PanIN-2 and PanIN-3 lesions, the rate of mutated K-ras increased to 45% and 56%, respectively. Apoptosis was present only in 2 of 26 PanIN-3 lesions. There was a gradual increase in proliferative activity from PanIN-1 to PanIN-3. p53 expression was found in 11% of PanIN-2 and 44% of PanIN-3 lesions. Bcl-2 expression was lacking in PanIN lesions of all grades. In invasive DACs, the apoptotic rate correlated with the degree of tumor differentiation and proliferation, with grade 3 carcinomas showing the highest apoptotic rate. Conclusion: In view of the discrepancy between the considerable rate of K-ras mutations in PanIN-1 and PanIN-2 lesions and the lack of apoptosis and Bcl-2 expression, coupled with very low p53 immunoreactivity, it is unlikely that mutated K-ras affects the apoptotic activity in low grade PanINs. Instead, K-ras mutations may have an effect on proliferation in PanIN-1 and PanIN-2.
Gesehen am 24.05.2022